Duty Hours Tracking – Is There an App for That? - Alexis Jorgensen (Journal of Medical Education and Curricular Development, 2022)
BACKGROUND To monitor duty hour compliance residency programs have used self-report methods which can be skewed by recall bias and data falsification. The purpose of this study was to compare the accuracy of and resident attitudes towards two duty hours tracking tools within our Orthopedic residency. We compared our institution's current self-report method of duty hours tracking via New Innovations (NI) with an automated method utilizing Hours Tracker (HT), a smartphone application which automatically logs work hours via GPS coordinates. The primary outcome measures were number of duty hour violations and survey results on resident perceptions. METHODS The participants were 22 residents of our 25 resident Orthopedic program. Over four weeks, residents tracked duty hours through the standard, selfreport method (NI) and simultaneously through the automated app (HT). Residents also completed an anonymous survey at the end of the study related to perceptions of the methods. RESULTS There was no significant difference in overall number of violations between NI and HT. HT detected more violations of the 8 hours off requirement (12 vs. 5, p = 0.03). Survey data revealed residents found HT significantly easier to use (p = .004) and less burdensome (p < .001) but in greater violation of privacy (p = .001). Residents reported they were more likely to falsify their hours when using NI (p = .002) and that the results of NI would be more likely used against them (p = .042). When analyzing by training year, junior residents indicated HT was overall easier to use than senior residents (p = .048). CONCLUSIONS Our study showed NI and HT are at least equivalent in accuracy with the app being overall better received, particularly by junior level residents. Until we begin accurately tracking duty hours and engaging residents with an easy to use, well-received interface to which report hours, effective developmental program changes will be difficult to achieve. An app-based approach is a starting point for re-thinking duty hours tracking within this digital age.